Las relaciones entre Estados Unidos y Rusia - Cámara Hermoso, Manuel De La (UNISCI Discussion Papers, 2007)
Although it is evident that neither in Washington nor in Moscow it is wished to recreate the Cold War, and there is no ideological confrontation like before, many regret the use of a Cold War rhetoric or, at least, the “cold peace” that the former two superpowers have entered. Russia’s image in the West has greatly deteriorated in the West during the past few months. But the reality is that Russia is there, and it still is a fundamental actor in the European and international context. The West must identify the failures and abuses and denounce them, but over all it must try to gradually extend to Russia the rules and institutions that fully guarantee prosperity and existing liberties in our countries.